IS THERE AN INSTRINSIC ALTERATION OF AORTIC MECHANICAL PROPERTIES IN BICUSPID AORTIC VALVE PATIENTS? REGIONAL COMPARISON WITH TRICUSPID AND MARFAN PATIENTS THROUGH 4D FLOW MRI. (June 2018) - Guala, A.; Dux-Santoy, L.; Ruiz-Muñoz, A.; Maldonado, G.; Teixidor-Tura, G.; Villalva, N.; Valente, F.; Gutierrez, L.; Galian, L.; Garcia-Dorado, D.; Evangelista, A.; Rodriguez-Palomares, J.
Abstract : Objective: Ascending aorta (AAo) dilation is highly prevalent in bicuspid aortic valve (BAV) patients. The etiology of dilation in BAV patients is widely discussed, with strong evidence for a role for both altered local hemodynamics (due to aortic valve morphology), and genetic factors. Current guidelines suggest to use a threshold of AAo diameter for the indication of prophylactic aortic resection. Nonetheless, as 40 % of dissection happen in non-dilated or mildly-dilated aorta, there is a clear need of new biomarkers. We aim to investigate whether regional aortic biomechanics are altered in BAV patients with respect to TAV and MFS individuals. Figure. No caption available. Design and method: We prospectively included 136 BAV, 44 Marfan and 54 TAV patients (including 18 with AAo aneurysm) without severe valvular disease. The 1.5T CMR protocol comprised a 4D flow MRI study to assess regional PWV, and cine CMR to compute AAo and DAo distensibility (AD). Three-dimensional geometry of the aorta were reconstructed from non-contrast-enhanced MR angiography and 100 analysis planes were identified. For each plane the average velocity waveform was extracted. The aorta was divided in AAo and descending aorta (DAo). The transit time between velocity waveforms was calculated with wavelet analysis of the systolic upslope. BAV population was divided in quintiles for maximum AAo diameter. Results: Once adjusted for age, blood pressure and local diameter, PWV and AD were similar in BAV and TAV subjects both in the presence (table 1) and in the absence (table 2) of AAo dilation. Differently, MFS patients presented lower distensibility and higher PWV in the AAo and DAo. PWV in BAV patients presented a biphasic trend with respect to the AAo diameter (see figure 1). There was a decrease of its value from 30 until 45 mm (first three quintiles). From this point the PWV increased with diameter. Differently, AD was conserved in the first three quintiles and decreased at larger diameters. Conclusions: Aortic biomechanics in BAV patients did not differ from TAV patients but are markedly different in Marfan patients. AAo PWV showed an initial decrease followed by a marked increase with respect to AAo diameter.